PENERAPAN MODEL KOOPERATIF TIPE JIGSAW PADA PEMBELAJARAN IPS DI SD - Sakuro, Akbar; Billa, Amanda Syahba; Fahsa, Aulia; Marini, Arita; Yunus, Mahmud (Cahaya Ilmu Bangsa Institute, 2024)
Social Sciences (IPS) learning in elementary schools in Indonesia has undergone a transformation from a teacher-centered lecture method to a student-centered approach, in order to improve the quality of learning and achieve national education goals. This research aims to determine the effectiveness of the Jigsaw type cooperative learning model in improving social studies learning outcomes in elementary schools. The method used is a literature review by analyzing various studies related to cooperative learning and the jigsaw model. The research results show that the application of the jigsaw model can improve social studies learning outcomes significantly, with consistent increases in learning achievement. This research also identified barriers to social studies learning, including limited teacher competence and student interest. Thus, the jigsaw type cooperative model has proven to be effective and can be an alternative for overcoming challenges in social studies learning in elementary schools. Pembelajaran Ilmu Pengetahuan Sosial (IPS) di sekolah dasar di Indonesia telah mengalami transformasi dari metode ceramah yang bersifat teacher-centered menjadi pendekatan student-centered, guna meningkatkan kualitas belajar dan mencapai tujuan pendidikan nasional. Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran kooperatif tipe Jigsaw dalam meningkatkan hasil belajar IPS di sekolah dasar. Metode yang digunakan adalah literature review dengan menganalisis berbagai kajian terkait pembelajaran kooperatif dan model jigsaw. Hasil penelitian menunjukkan bahwa penerapan model jigsaw dapat meningkatkan hasil belajar IPS secara signifikan, dengan peningkatan prestasi belajar yang konsisten. Penelitian ini juga mengidentifikasi hambatan dalam pembelajaran IPS, termasuk keterbatasan kompetensi guru dan minat siswa. Dengan demikian, model kooperatif tipe jigsaw terbukti efektif dan dapat menjadi alternatif untuk mengatasi tantangan dalam pembelajaran IPS di sekolah dasar.